First Do No Harm (online): When Healthcare Practitioners Become Agents of Information Pollution - Lavorgna, Anita (European journal on criminal policy and research, 2025)
Over the last decade, the creation and dissemination of health-related information pollution has been investigated as a topic of criminological concern, especially in its manifestation as a distinguishing criminogenic and harming feature of life in cyberspace. This contribution furthers this line of inquiry by focusing on health-related information pollution disseminated online by healthcare practitioners. This phenomenon has severe implications in terms of healthcare practitioners’ ethical and professional responsibility, and public trust. By examining how current regulatory practices in both Italy and the UK are only recently starting to acknowledge the issue of healthcare practitioners involved in the creation and propagation of health-related information pollution, and are still doing so in a partial and ineffective way, this article discusses how, in the social media platforms facilitating the spreading of health-related information pollution, the boundaries between personal and professional use are blurred, yet they both shape public identities; this entails specific challenges when it comes to possible management or mitigation strategies.